Potensi Tanaman Obat Tradisional Indonesia sebagai Agen Bio Aktif Penunjang Kesehatan Tulang - Cut Massyitah Thaib; Artha Sianipar; Siti Nurbaya; Katarina Riris Teresia; Ade Irma Suryani; Eva Diansari Marbun (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Abstrak. Osteoporosis is a degenerative bone disease characterized by a decrease in bone mass and strength, particularly in postmenopausal women. Traditional plant-based therapy presents an attractive alternative given the rich local bioactive potential and limited access to pharmacological treatments. One important biochemical indicator in bone regeneration is the level of alkaline phosphatase (ALP). The aim of this study is to evaluate the potential of various Indonesian traditional medicinal plants as bioactive agents in the prevention of osteoporosis, with an emphasis on increasing ALP levels. This method employed a literature search by collecting several scientific articles discussing the anti-osteoporosis activity of traditional medicinal plants through in vitro, in vivo, and clinical observation studies. The results obtained show that traditional medicinal plants such as Turmeric (Curcuma longa), Black pepper (Piper nigrum), Bromelain (Ananas comosus), Papaya (Carica papaya), Japanese knotweed (Reynoutria japonica Houtt.), Veratrum nigrum, Sickle senna (Cassia tora), Red ginger (Zingiber officinale var. rubrum), Clove (Syzygium aromaticum L.), White turmeric (Curcuma zeadoaria), and Celery (Apium graveolens) are capable of reducing the number of osteoclasts and promoting bone formation. These findings consistently demonstrate a positive role in bone health through increased ALP levels. Indonesian traditional medicinal plants hold great potential as evidence-based anti-osteoporosis agents, particularly through enhancing ALP levels and osteoblast activity. This literature review supports the development of local herbal therapy as a promotive and preventive alternative against osteoporosis.